2020
DOI: 10.1021/acs.jpcc.0c00617
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Anticorrosive Zinc Coatings: Tuning the Adhesion of Zinc/Silica Contact by Interfacial Ternary Oxide Formation

Abstract: Formation of mixed compounds at interfaces between materials often has significant impact on the properties of the junction. With the goal of assessing if interfacial oxide mixing improves the adhesion of anti-corrosive zinc coatings on silica, we report an ab initio study of the structural, electronic, and adhesion characteristics of interfaces between zinc and zinc silicate. We show that, regardless the precise thermodynamic conditions, ZnO-rich zinc silicate interfaces are more stable than SiO 2-rich ones b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…34 Therefore, we have estimated to what extent the interfacial charge transfer and the partial metal ionization impact the bonding within the different metal deposits. In previous studies, this effect was found to be significant only at oxygen-rich interfaces 37 , and the minimal separation energy was reached when a number of metal atoms close to that needed to compensate the surface polarity was left on the oxide surface. 34 Therefore, we have tested whether the separation energies decrease when one metal atom per O 2− 2 group is left on the silica surface, breaking the peroxo group and compensating the surface polarity.…”
Section: Metal Decohesionmentioning
confidence: 86%
See 3 more Smart Citations
“…34 Therefore, we have estimated to what extent the interfacial charge transfer and the partial metal ionization impact the bonding within the different metal deposits. In previous studies, this effect was found to be significant only at oxygen-rich interfaces 37 , and the minimal separation energy was reached when a number of metal atoms close to that needed to compensate the surface polarity was left on the oxide surface. 34 Therefore, we have tested whether the separation energies decrease when one metal atom per O 2− 2 group is left on the silica surface, breaking the peroxo group and compensating the surface polarity.…”
Section: Metal Decohesionmentioning
confidence: 86%
“…We recall here that the interface energies between TMOs and metals E , but considering the low values normally found for oxide/oxide interface energies 37,39 (often in the range 0.5-1.0 J m −2 ) we expect ∆E buf to be significantly negative. As a consequence, the segregation of TMOs near silica will be thermodynamically favored.…”
Section: Stainless Steel Buffers At the Sio 2 /Zn Interfacementioning
confidence: 88%
See 2 more Smart Citations
“…Zinc silicate (Zn 2 SiO 4 ) exhibits several desirable characteristics, such as low toxicity, cost-effectiveness, and excellent physical and chemical stability. , Owing to these attributes, Zn 2 SiO 4 commonly acts as a protective barrier between metal surfaces and corrosive environments, , and is widely used as a corrosion-resistant filler of epoxy resin in the field of metal corrosion protection. , However, the presence of micro gaps in Zn 2 SiO 4 coatings reduced their shielding performance, leading to decreased long-term corrosion resistance. In recent years, the scientific community has shown significant interest in nanocomposites that incorporate materials such as graphene, graphene oxide (GO), polyaniline, and polydopamine (PDA) to fill the micropores of Zn 2 SiO 4 material.…”
Section: Introductionmentioning
confidence: 99%